PENERAPAN PEMBELAJARAN DIFERENSIASI UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA FASE C SDN 03 KALIRANDU - Rahmadani, Dhiva; Nugraheni, Nursiwi (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
This research is classroom action research whose results are an increase in student learning outcomes in whole number material up to 100,000. This research was carried out in Phase C of SDN 03 Kalirandu, Petarukan District, Pemalang Regency in the odd semester of the 2023/2024 academic year. The subjects of this research were Phase C students at SDN 03 Kalirandu. The data collection method uses descriptive quantitative analysis techniques. The results of this research are an increase in pre-cycle learning outcomes to cycle I learning outcomes by 37% and an increase in cycle I learning outcomes to cycle II learning outcomes by 6%. Based on the research results, it can be concluded that classroom action research using differentiation learning in the classroom can improve mathematics learning outcomes in phase C in whole number material up to 100,000 SDN 03 Kalirandu.